2022
DOI: 10.1136/emermed-2021-211660
|View full text |Cite
|
Sign up to set email alerts
|

Impact of pharmacist interventions provided in the emergency department on quality use of medicines: a systematic review and meta-analysis

Abstract: BackgroundPharmacists have an increasing role as part of the emergency department (ED) team. However, the impact of ED-based pharmacy interventions on the quality use of medicines has not been well characterised.ObjectiveThis systematic review aimed to synthesise evidence from studies examining the impact of interventions provided by pharmacists on the quality use of medicines in adults presenting to ED.MethodsA systematic literature search was conducted in MEDLINE, EMBASE and CINAHL. Two independent reviewers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 44 publications
2
16
0
Order By: Relevance
“…These results show that by practical implementation of a medication review program at the ED, comparable DRP rates are found as in literature. In a recently published meta-analysis, the impact of pharmacist interventions in the ED were studied [ 12 ]. Overall, by pharmacist interventions the percentage of patients with at least one medication error was reduced by 73% and the mean number of medication errors per patient was reduced by 0.33.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results show that by practical implementation of a medication review program at the ED, comparable DRP rates are found as in literature. In a recently published meta-analysis, the impact of pharmacist interventions in the ED were studied [ 12 ]. Overall, by pharmacist interventions the percentage of patients with at least one medication error was reduced by 73% and the mean number of medication errors per patient was reduced by 0.33.…”
Section: Discussionmentioning
confidence: 99%
“…Although its impact on mortality was limited [ 5 , 8 , 9 ], other studies have indicated shorter hospital stays, reduced ED visits, heightened patient satisfaction, and decreased healthcare costs [ 5 , 10 11 ]. Additionally, pharmacist interventions in the ED was linked to more accurate and thorough medication histories, and higher prescription appropriateness [ 12 ]. While the effects of in-hospital medication reviews have been well-researched, the impact of medication reviews for older patients living with frailty in the ED has yet to be fully studied.…”
Section: Introductionmentioning
confidence: 99%
“…Two reviews included patient populations with cardiovascular disease and/ or other chronic conditions [15,16]. Four reviews included restricted settings: two included studies based only in hospital [18,31], one in care homes [13], and another ambulatory care [30].…”
Section: Description Of Extent and Range Of Pharmacist-led Medication...mentioning
confidence: 99%
“…Evidence for MRs having a positive effect on medication-related problems is inconclusive due to mixed results. Reviews reported that pharmacists were able to identify medicines-related problems [8, 9,11,13,14,19,20,22,31]; this was quanti ed in ve of these reviews [8,11,13,20,26] with the remaining reviews reporting this in results or discussion. However, the resolution of medicines-related problems was not reported or yielded mixed results.…”
Section: Reported Outcomes and Evidence For Effectiveness Of Medicati...mentioning
confidence: 99%
See 1 more Smart Citation